DEMONSTRASI DAN DAN TRI DHARMA PERGURUAN TINGGI; JALAN PENGABDIAN DI BAWAH TEKANAN DAN POLITISASI - Muhammad Fajri; Siti Bunnayah (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2020)
Demonstrations are the arteries in a democratic country. In a democratic state system there is freedom of expression in public, one of which can be in the form of demonstrations. However, in the course of democracy still faces many obstacles in its application. Demonstrations have been and have been carried out by the people in controlling the running of the government in Indonesia, but not a few of the treatments of the demonstrators and demonstration activities have come under pressure. If demonstrations are held against the government, they are often politicized and the chain suppression is carried out. In fact, in the context of a democratic state, demonstrations are protected by the Law and there are rules. And so it is with demonstrations outside of the (anarchist) Corporations Act also has set sanctions. The method used in analyzing by collecting some reading and factual data, then analyzed how the actual position of the demonstration in a country that adheres to a democratic system. By understanding the nature of a democracy, a democratic state and demonstrations and the substance of the Tri Dharma of higher education, the demonstration is "halal" in the context of a democratic state, and that is also part of the form of community service as contained in the Tri Dharma College. So, the Demonstration is one place for students to do one of the Tri Dharma of higher education, namely "Community Service", as well as being an instrument for community empowerment